Influence of Kartogenin on Chondrogenic Differentiation of Human Bone Marrow-Derived MSCs in 2D Culture and in Co-Cultivation with OA Osteochondral Explant - Timea Spakova; Jana Plsikova; Denisa Harvanova; Marek Lacko; Stefan Stolfa; Jan Rosocha (Molecules, 2018)
Articular cartilage has limited capacity for natural regeneration and repair. In the present study, we evaluated kartogenin (KGN), a bioactive small heterocyclic molecule, for its effect on in vitro proliferation and chondrogenic differentiation of human bone marrow-derived mesenchymal stromal cells (hBMSCs) in monolayer culture and in co-culture models in vitro. OA osteochondral cylinders and hBMSCs were collected during total knee replacement. The effect of KGN on hBMSCs during 21 days of culture was monitored by real-time proliferation assay, immunofluorescence staining, histological assay, scanning electron microscopy (SEM) (imaging and multiplex enzyme-linked immunosorbent assay) ELISA assay. The rate of proliferation of hBMSCs was significantly increased by treatment with 10 µM KGN during nine days of culture. Histological and SEM analyses showed the ability of hBMSCs in the presence of KGN to colonize the surface of OA cartilage and to produce glycosaminoglycans and proteoglycans after 21 days of co-culture. KGN treated hBMSCs secreted higher concentrations of TIMPs and the secretion of pro-inflammatory molecules (MMP 13, TNF-α) were significantly suppressed in comparison with control without hBMSCs. Our preliminary results support the concept that 10 µM KGN enhances proliferation and chondrogenic differentiation of hBMSCs and suggest that KGN is a potential promoter for cell-based therapeutic application for cartilage regeneration.